Correlated perturbations from inflation and the cosmic microwave background - Amendola, Luca (Physical review letters, 2002)
We compare the latest cosmic microwave background data with theoretical predictions including correlated adiabatic and cold dark matter (CDM) isocurvature perturbations with a simple power-law dependence. We find that there is a degeneracy between the amplitude of correlated isocurvature perturbations and the spectral tilt. A negative (red) tilt is found to be compatible with a larger isocurvature contribution. Estimates of the baryon and CDM densities are found to be almost independent of the isocurvature amplitude. The main result is that current microwave background data do not exclude a dominant contribution from CDM isocurvature fluctuations on large scales.
Gesehen am 17.11.2017